Optical Film

A film with ester resin and a wavelength dispersion adjuster addresses the complexity and transparency issues of existing retardation films, providing enhanced reverse wavelength dispersion and optical performance.

JP7601187B2Active Publication Date: 2024-12-17TOSOH CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023192679
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2024-12-17
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

Existing methods for manufacturing retardation films are complicated, leading to poor productivity and difficulty in controlling uniformity of phase difference, and existing films with negative birefringence have issues with transparency and wavelength dependence.

Method used

An optical film composed of an ester resin with negative birefringence and a wavelength dispersion adjuster with positive birefringence, where the refractive indices satisfy nx

Benefits of technology

The film exhibits excellent reverse wavelength dispersion characteristics, suitable for use in liquid crystal displays and antireflection films, with improved viewing angle and optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601187000001
    Figure 0007601187000001
  • Figure 0007601187000002
    Figure 0007601187000002
  • Figure 0007601187000003
    Figure 0007601187000003
Patent Text Reader

Abstract

To provide a retardation film which exhibits excellent visual field angle characteristics and wavelength dispersion characteristics in a thin film, from a viewpoint of compatibility to thinning of an optical member.SOLUTION: An optical film contains an ester-based resin exhibiting negative birefringence and a wavelength dispersion modifier exhibiting positive wavelength dispersion, wherein a refractive index in a fast phase axis direction in a film plane is represented by nx, a refractive index in a film in-plane direction perpendicular thereto is represented by ny, and a refractive index in a vertical direction outside the film plane is represented by nz, a relation among them is nx<ny≤nz, and a ratio (R450 / R50) of an in-plane retardation (R450) measured at a wavelength of 450 nm represented by a following expression (a) to an in-plane retardation (R550) measured at a wavelength of 550 nm is 1.00 or less. Re=(ny-nx)×d (a), (wherein, nx represents a refractive index in a fast phase axis direction in a film plane, ny represents a refractive index in a slow phase axis direction in the film plane, nz represents a refractive index in a vertical direction outside the film plane, and d represents a thickness of the film).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an optical film that can be suitably used as a retardation film, and more particularly to an optical film that is excellent in retardation properties and wavelength dependency. [Background technology]

[0002] Liquid crystal displays are the most important display devices in our multimedia society, and are used in a wide range of applications, from mobile phones and computer monitors to laptops and televisions. Many optical films are used in liquid crystal displays to improve their display characteristics. In particular, optical films play an important role in improving contrast and compensating for color tones when viewed from the front or at an angle. A typical example of an optical film for liquid crystal displays is a retardation film, which is used as an anti-reflection layer for reflective liquid crystal displays, touch panels, and organic electroluminescence (EL) displays.

[0003] Conventional retardation films are made of polycarbonate or cyclic polyolefin, both of which have positive birefringence. Here, the positive and negative birefringence are defined as follows: The optical anisotropy of a polymer film that has been molecularly oriented by stretching or other means can be represented by an index ellipsoid, where nx is the refractive index in the fast axis direction in the film plane when the film is stretched, ny is the refractive index in the in-plane direction perpendicular to nx, and nz is the refractive index in the thickness direction of the film.

[0004] In other words, when a polymer with negative birefringence is uniaxially stretched, the refractive index is small in the direction of the stretching axis (fast axis: stretching direction), and when a polymer with positive birefringence is uniaxially stretched, the refractive index is small in the direction perpendicular to the stretching axis (fast axis: direction perpendicular to the stretching direction). The in-plane retardation (Re) is expressed as the value obtained by multiplying the refractive index in the direction perpendicular to the fast axis (ny) minus the refractive index in the fast axis direction (nx) by the thickness of the film.

[0005] Many polymers have positive birefringence. Polymers with negative birefringence include acrylic resin and polystyrene, but acrylic resin has low retardation and is not sufficient for optical compensation film. Polystyrene is not currently used due to problems with retardation stability, such as a large photoelastic coefficient at room temperature that causes the retardation to change with even a slight stress, optical properties such as a large wavelength dependency of retardation, and practical problems such as low heat resistance.

[0006] The wavelength dependency of retardation means that the retardation changes depending on the measured wavelength, and can be expressed as the ratio R450 / R550, which is the ratio of the retardation (R450) measured at a wavelength of 450 nm to the retardation (R550) measured at a wavelength of 550 nm. In general, in polymers with aromatic structures, this R450 / R550 tends to be large, and the contrast and viewing angle characteristics in the low wavelength region are reduced. In this application, a retardation film (hereinafter referred to as "reverse wavelength dispersion film") is required in which the in-plane retardation R450 / R550 is 1.00 or less, which is particularly large in the long wavelength region.

[0007] A stretched polymer film exhibiting negative birefringence has a high refractive index in the thickness direction of the film and can be used as an unprecedented optical compensation film. For example, it is useful as a retardation film for compensating the viewing angle characteristics of displays such as super twisted nematic liquid crystal displays (STN-LCDs), vertically aligned liquid crystal displays (VA-LCDs), in-plane aligned liquid crystal displays (IPS-LCDs), reflective liquid crystal displays, and semi-transmissive liquid crystal displays, or as a retardation film for compensating the viewing angle of polarizing plates, and there is strong demand in the market for retardation films with negative birefringence.

[0008] In order to meet such requirements, various retardation films have been developed. Methods for producing a film in which a refractive index in the thickness direction of the film is increased by using a polymer having positive birefringence have been proposed. One method is a treatment method in which a heat-shrinkable film is adhered to one or both sides of a polymer film, and the laminate is heat-stretched to apply a shrinking force in the thickness direction of the polymer film (see, for example, Patent Documents 1 to 3). Another method has been proposed in which an electric field is applied to the polymer film while the film is uniaxially stretched in-plane (see, for example, Patent Document 4). In addition, a retardation film made of fine particles having negative optical anisotropy and a transparent polymer has been proposed (see, for example, Patent Document 5). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 2818983 [Patent Document 2] Japanese Patent Application Publication No. 05-297223 [Patent Document 3] Japanese Patent Application Publication No. 05-323120 [Patent Document 4] Japanese Patent Application Publication No. 06-088909 [Patent Document 5] JP 2005-156862 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, the methods proposed in Patent Documents 1 to 4 have problems such as poor productivity due to the extremely complicated manufacturing process, and the control of the uniformity of retardation and the like is significantly more difficult than with conventional stretching. In addition, the optical compensation film obtained in Patent Document 5 is a retardation film having negative birefringence due to the addition of fine particles having negative optical anisotropy, and has problems with uniform dispersion of the fine particles, uniform orientation control, film transparency, etc.

[0011] No practical examples of films exhibiting inverse wavelength dispersion and having a resin with negative birefringence as the main component have been known. Such a retardation film, when combined with a thin film of polycarbonate or polyarylate exhibiting positive birefringence, can exhibit a high in-plane retardation while being a thin film, and can be adjusted to an arbitrary out-of-plane retardation, thereby realizing a film excellent in inverse wavelength dispersion.

Means for Solving the Problems

[0012] As a result of intensive studies by the present inventors, it has been found that an optical film using an ester resin having specific properties and a wavelength dispersion adjuster satisfies the above problems, and the present invention has been completed.

[0013] That is, the present invention contains an ester resin exhibiting negative birefringence and a wavelength dispersion adjuster exhibiting positive birefringence. When the refractive index in the advancing axis direction in the film plane is nx, the refractive index in the in-plane direction orthogonal thereto is ny, and the refractive index in the vertical direction outside the film plane is nz, the respective relationships are nx < ny ≦ nz, and the ratio (R450 / R550) of the in-plane retardation (R450) measured at a wavelength of 450 nm and the in-plane retardation (R550) measured at a wavelength of 550 nm shown by the following formula (a) is 1.00 or less. The present invention relates to an optical film. Re = (ny - nx) × d (a) (In the formula, nx represents the refractive index in the advancing axis direction in the film plane, ny represents the refractive index in the slow axis direction in the film plane, nz represents the refractive index in the vertical direction outside the film plane, and d represents the thickness of the film.)

Effects of the Invention

[0014] According to the present invention, since it exhibits specific retardation characteristics and inverse wavelength dispersion characteristics in a thin film close to a single component, it is useful as an optical film for liquid crystal displays or an antireflection film.

Modes for Carrying Out the Invention

[0015] Hereinafter, an optical film which is one aspect of the present invention (hereinafter referred to as "the optical film of the present invention") will be described in detail.

[0016] The optical film of the present invention contains an ester resin exhibiting negative birefringence and a wavelength dispersion adjuster exhibiting positive birefringence. When the refractive index in the fast axis direction within the film plane is nx, the refractive index in the direction within the film plane orthogonal thereto is ny, and the refractive index in the vertical direction outside the film plane is nz, the respective relationships are nx < ny ≤ nz, and the ratio (R450 / R550) of the in-plane retardation (R450) measured at a wavelength of 450 nm and the in-plane retardation (R550) measured at a wavelength of 550 nm, which is represented by the following formula (a), is 1.00 or less. It is an optical film (hereinafter also referred to as "film (A)"). Re = (ny - nx) × d (a) (In the formula, nx represents the refractive index in the fast axis direction within the film plane, ny represents the refractive index in the slow axis direction within the film plane, nz represents the refractive index in the vertical direction outside the film plane, and d represents the thickness of the film.)

[0017] A film having a relationship of refractive indices nx, ny, nz such that nx < ny ≤ nz can be obtained, for example, by uniaxially stretching a polymer having negative birefringence. Here, the positive and negative of birefringence are defined as follows.

[0018] Negative birefringence means that the stretching direction is the fast axis direction, and positive birefringence means that the direction perpendicular to the stretching direction is the fast axis direction. That is, a resin exhibiting positive birefringence is one in which the refractive index in the direction perpendicular to the stretching axis becomes small (fast axis: direction perpendicular to the stretching direction) when uniaxially stretched, and a resin exhibiting negative birefringence is one in which the refractive index in the stretching axis direction becomes small (fast axis: stretching direction) when uniaxially stretched.

[0019] When a resin exhibiting positive birefringence and a resin exhibiting negative birefringence are stretched, a difference in refractive index occurs in the axial direction perpendicular to the stretching direction, and an in-plane retardation (Re) is generated. Re is expressed by the following formula (a). Furthermore, a resin exhibiting positive birefringence has a small refractive index in the thickness direction perpendicular to the stretching direction, and therefore an out-of-plane retardation (Rth) becomes positive and large. On the other hand, a resin exhibiting negative birefringence has a large refractive index in the thickness direction perpendicular to the stretching direction, and therefore an out-of-plane retardation (Rth) becomes negative and large. Rth is expressed by the following formula (b). Re = (ny-nx) × d (a) Rth = [(nx + ny) / 2 - nz] × d (b) (In formulas (a) and (b), d represents the thickness of the film.)

[0020] The optical film of the present invention is characterized by comprising a composition containing an ester resin having negative birefringence and a wavelength dispersion regulator having positive birefringence. The combination of negative and positive birefringence of the materials constituting the composition makes it possible to control wavelength dispersion. The composition configuration makes it possible to exhibit excellent reverse wavelength dispersion characteristics, in which the wavelength dispersion characteristics expressed by R450 / R550, the in-plane retardation (R450) measured at a wavelength of 450 nm and the in-plane retardation (R550) measured at a wavelength of 550 nm, are 1.00 or less (hereinafter referred to as "wavelength dispersion characteristics").

[0021] In order to realize the reverse wavelength dispersion characteristic, a combination of negative and positive birefringence is generally required. Therefore, when controlling the wavelength dispersion of a resin having positive birefringence to reverse wavelength dispersion, a wavelength dispersion regulator having negative birefringence is required, but it is not easy to realize negative birefringence in which the refractive index increases in the axial direction perpendicular to the stretching direction, and it is even more difficult with low molecular weight components such as additives that reduce the orientation. On the other hand, in the configuration of the optical film of the present invention, the wavelength dispersion of the resin having negative birefringence is adjusted using a wavelength dispersion control agent having positive birefringence. Positive birefringence, which has a large refractive index in the stretching direction, can be expressed even with a low molecular weight of an additive, and is likely to express large wavelength dispersion characteristics. Therefore, by adjusting the wavelength dispersion of the resin having negative birefringence using a wavelength dispersion control agent having positive birefringence, it is possible to express reverse wavelength dispersion characteristics.

[0022] The wavelength dispersion characteristic of the optical film of the present invention is 1.00 or less, preferably Re(450) / Re(550)≦0.99, and more preferably Re(450) / Re(550)≦0.98. Here, the wavelength dispersion characteristic Re(450) / Re(550) is a value calculated by dividing the value Re(450) measured at a wavelength of 450 nm by the value Re(550) measured at a wavelength of 550 nm using a general automatic birefringence meter.

[0023] A wavelength dispersion regulator showing positive birefringence is an additive having positive birefringence and larger wavelength dispersion characteristics than an ester resin showing negative birefringence. Since it has a large positive wavelength dispersion characteristic and has an excellent wavelength dispersion adjustment function, it is preferably an aromatic compound. Preferred examples include benzotriazole-based compounds, benzophenone-based compounds, triazine-based compounds, benzoate-based compounds, polyphenyl-based compounds, etc. As the wavelength dispersion regulator, at least one of triazine-based compounds and polyphenyl-based compounds is preferable because it has a large positive wavelength dispersion.

[0024] From the viewpoints of compatibility with the resin, in-plane retardation, and wavelength dispersion adjustment, the wavelength dispersion regulator preferably has a molecular weight of 100 to 30,000, more preferably 300 to 10,000, and particularly preferably 300 to 1,000. Here, the molecular weight refers to the molecular weight if the wavelength dispersion regulator is a low molecular weight compound that can be calculated from the chemical structure, and refers to the weight average molecular weight calculated in terms of standard polystyrene if the wavelength dispersion regulator is a polymer compound having repeating units.

[0025] The ratio of the wavelength dispersion regulator in the composition contained in the optical film of the present invention is 0.01 to 30% by weight, preferably 0.1 to 15% by weight, and more preferably 0.3 to 10% by weight, from the viewpoints of improving mechanical properties, in-plane retardation, and adjusting wavelength dispersion.

[0026] Examples of wavelength dispersion regulators used in the present invention include benzotriazole-based compounds such as 2-(2'-hydroxy-5'-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]benzotriazole, 2,2'-methylenebis[6-(benzotriazol-2-yl)-4-t-octylphenol], and 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol; and benzophenone-based compounds such as 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, and 2-hydroxy-4-methoxy-5-sulfobenzophenone. Triazine compounds such as 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine, and 2,6-diphenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine. Benzoate compounds such as 2,4-di-t-butylphenyl-3,5-di-t-butyl-4-hydroxybenzoate, 2,4-di-t-pentylphenyl-3,5-di-t-butyl-4-hydroxybenzoate, and hexadecyl-3,5-di-t-butyl-4-hydroxybenzoate.Examples of polyphenyl compounds include N,N,N',N'-tetraphenylbenzidine, N,N'-diphenyl-N,N'-di(o-tolyl)benzidine, N,N'-diphenyl-N,N'-di(m-tolyl)benzidine, N,N'-diphenyl-N,N'-di(p-tolyl)benzidine, N,N'-bis(4-formylphenyl)-N,N'-diphenylbenzidine, N,N'-di(4-biphenylyl)-N,N'-diphenylbenzidine, N,N'-bis(4-methoxy-2-methylphenyl)-N,N'-diphenylbenzidine, 4-cyano-4''-propyl-p-terphenyl, 4-cyano-4''-pentyl-p-terphenyl, 4-amino-p-terphenyl, 4,4''-diamino-p-terphenyl, and 4,4''-dihydroxy-p-quaterphenyl.

[0027] As an example of an ester resin having negative birefringence, preferred from the standpoints of heat resistance and transparency, is a fumaric acid ester resin. The fumaric acid ester-based resin includes a polymer of a fumaric acid ester, and among them, it is preferable that the polymer contains a fumaric acid diester residue unit represented by the following formula (1).

[0028] [ka]

[0029] (In the formula, R1 and R2 each independently represent one of the group consisting of a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cyclic alkyl group having 3 to 6 carbon atoms).

[0030] When the fumarate ester resin contains a fumarate diester residue unit represented by formula (1), it preferably contains 50 mol % or more of the residue unit.

[0031] In formula (1), R1 and R2 are each independently a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cyclic alkyl group having 3 to 6 carbon atoms. The alkyl group may be substituted with a halogen group such as a fluorine atom or a chlorine atom, an ether group, an ester group, or an amino group. Specific examples of R1 and R2 include an ethyl group, an isopropyl group, an s-butyl group, a t-butyl group, an s-pentyl group, a t-pentyl group, an s-hexyl group, a t-hexyl group, a cyclopropyl group, a cyclopentyl group, and a cyclohexyl group. Among these, a member of the group consisting of an ethyl group, an isopropyl group, an s-butyl group, a t-butyl group, a cyclopentyl group, and a cyclohexyl group is preferred in order to provide a retardation film having excellent heat resistance and mechanical properties. In particular, an isopropyl group is preferred in order to provide a retardation film having an excellent balance between heat resistance and mechanical properties.

[0032] Specific examples of the fumarate diester residue unit represented by formula (1) include diisopropyl fumarate residue, di-s-butyl fumarate residue, di-t-butyl fumarate residue, di-s-pentyl fumarate residue, di-t-pentyl fumarate residue, di-s-hexyl fumarate residue, di-t-hexyl fumarate residue, dicyclopropyl fumarate residue, dicyclopentyl fumarate residue, dicyclohexyl fumarate residue, and the like, of which diisopropyl fumarate residue, di-s-butyl fumarate residue, di-t-butyl fumarate residue, dicyclopentyl fumarate residue, dicyclohexyl fumarate residue, and the like are preferred, and diisopropyl fumarate residue is particularly preferred.

[0033] The fumaric acid diester resin may contain one residue unit represented by formula (1), or may contain two or more types of residue units represented by formula (1), i.e., two or more components.

[0034] The fumaric acid ester resin used in the present invention is preferably a resin containing 50 mol% or more of fumaric acid diester residue units represented by formula (1) and 50 mol% or less of residue units consisting of monomers copolymerizable with fumaric acid diesters. Here, examples of the residue units consisting of monomers copolymerizable with fumaric acid diesters include styrene residues such as styrene residues and α-methylstyrene residues; acrylic acid residues; acrylic acid ester residues such as methyl acrylate residues, ethyl acrylate residues, and butyl acrylate residues; methacrylic acid residues; methacrylic acid ester residues such as methyl methacrylate residues, ethyl methacrylate residues, and butyl methacrylate residues; vinyl ester residues such as vinyl acetate residues and vinyl propionate residues; acrylonitrile residues; methacrylonitrile residues; olefin residues such as ethylene residues and propylene residues; and the like, which may be one or more of the following: Among them, the fumaric acid diester residue unit represented by the general formula (1) is preferably 70 mol % or more, and in order to obtain a retardation film having particularly excellent heat resistance and mechanical properties, the fumaric acid diester residue unit is preferably 80 mol % or more, and more preferably 90 mol % or more.

[0035] Ester resins have particularly excellent mechanical properties and excellent processability during film formation. Therefore, they are suitable for use in films with a number average molecular weight (Mn) of 1×10 based on standard polystyrene standards, as determined from the elution curve measured by gel permeation chromatography (GPC). 3 ~5×10 6 Preferably, it is 5×10 3 ~3×10 5 It is even more preferable that:

[0036] The ester resin may be produced by any method as long as the copolymer can be obtained, and may be produced by radical polymerization. As the radical polymerization method, for example, any of bulk polymerization method, solution polymerization method, suspension polymerization method, precipitation polymerization method, emulsion polymerization method, and the like can be used.

[0037] From the viewpoint of suitability for thinning optical members, the optical film of the present invention has a thickness of preferably 0.1 μm to 79.9 μm, more preferably 0.1 μm to 34.9 μm, and most preferably 0.1 μm to 19.9 μm.

[0038] The Re measured at 589 nm of the optical film of the present invention is preferably 120 nm or more and 700 nm or less, more preferably 130 nm or more and 500 nm or less, and particularly preferably 130 nm or more and 350 nm or less, since the optical film becomes a retardation film with excellent optical properties. The optical film of the present invention has an Rth measured at 589 nm of preferably −700 nm or more and −60 nm or less, more preferably −350 nm or more and −65 nm or less, and particularly preferably −200 nm or more and −65 nm or less, since the optical film of the present invention has excellent viewing angle characteristics.

[0039] Hereinafter, the laminate film according to one embodiment of the present invention (hereinafter referred to as "the laminate film of the present invention") will be described in detail.

[0040] The optical film of the present invention (hereinafter referred to as "film (A)") exhibits excellent viewing angle characteristics and reverse wavelength dispersion characteristics when laminated with a film exhibiting positive birefringence (hereinafter referred to as "film (B)").

[0041] Because the Rth of film (A) has a negative value and the Rth of film (B) has a positive value, it is possible to adjust the Rth to any value when laminated. Furthermore, because film (B) has positive wavelength dispersion characteristics, it is possible to adjust the wavelength dispersion characteristics when films (A) and (B) are laminated to a larger reverse wavelength dispersion characteristic.

[0042] Unlike materials having a normal negative birefringence of Re(450) / Re(550)>1.00, the film (A) of the present invention has reverse wavelength dispersion characteristics, and therefore, when laminated with the film (B), it is possible to achieve a thinner film with large reverse wavelength dispersion characteristics. The wavelength dispersion characteristics of the laminated film of the present invention can be controlled by adjusting the wavelength dispersion characteristics and Re of the films (A) and (B). To suppress color shift, it is preferable that 0.80≦Re(450) / Re(550)≦0.90, more preferably 0.81≦Re(450) / Re(550)≦0.87, and particularly preferably 0.82≦Re(450) / Re(550)≦0.86.

[0043] From the viewpoint of suitability for thin optical members, the thickness of the laminated film of the present invention is preferably 80 μm or less, more preferably 0.2 μm to 50 μm, and most preferably 0.2 μm to 40 μm.

[0044] The Re of the laminated film of the present invention can be controlled by adjusting the Re of the film (A) and the film (B). Since the laminated film of the present invention has better optical properties when used as a retardation film, the Re is preferably 120 nm or more and 300 nm or less, more preferably 130 nm or more and 300 nm or less, and particularly preferably 130 nm or more and 280 nm or less. The Rth of the laminated film of the present invention can be controlled by adjusting the Rth of the film (A) and the film (B). Since the laminated film of the present invention has excellent viewing angle compensation performance when used as a retardation film, the Rth is preferably from -300 nm to 10 nm, more preferably from -100 nm to 10 nm, and particularly preferably from -10 nm to 10 nm.

[0045] From the viewpoint of suitability for thinning optical members, the thickness of film (B) is preferably 0.1 μm to 79.9 μm, more preferably 0.1 μm to 19.9 μm, and most preferably 0.1 μm to 9.9 μm.

[0046] The Re of film (B) is preferably 20 nm or more and 400 nm or less, more preferably 20 nm or more and 250 nm or less, and particularly preferably 20 nm or more and 200 nm or less, since a thinner retardation film having excellent optical properties is obtained when film (A) and film (B) are laminated together. Since a retardation film having a thinner film and excellent viewing angle characteristics is obtained when the film (A) and the film (B) are laminated, the Rth of the film (B) is preferably 10 nm or more and 800 nm or less, more preferably 10 nm or more and 200 nm or less, and particularly preferably 10 nm or more and 100 nm or less.

[0047] The wavelength dispersion characteristics of film (B) are preferably 1.07≦Re(450) / Re(550), more preferably 1.09≦Re(450) / Re(550), and particularly preferably 1.10≦Re(450) / Re(550), since the larger the positive wavelength dispersion, the thinner the film and the better the reverse wavelength dispersion characteristics that can be exhibited when films (A) and (B) are laminated together.

[0048] Such a film (B) can be obtained, for example, by uniaxially stretching a polymer having positive birefringence. The polymer having positive birefringence is not particularly limited as long as it is a polymer having positive birefringence, and preferred examples from the viewpoints of heat resistance and transparency include polycarbonate resins, polyethersulfone resins, polyarylate resins, polyimide resins, cyclic olefin resins, cellulose resins, and N-substituted maleimide resins. Among these, films having large positive wavelength dispersion, such as polycarbonate resins, polyethersulfone resins, polyarylate resins, and polyimide resins, are preferred, since a retardation film having reverse wavelength dispersion can be obtained when laminated with film (A). The angle between the fast axis of film (A) and the fast axis of film (B) can be set according to the purpose, and among them, since a thinner film exhibits excellent reverse wavelength dispersion characteristics during lamination and productivity is increased, the angle is preferably 90 degrees ± 20 degrees or less, more preferably 90 degrees ± 5 degrees or less, and particularly preferably 90 degrees ± 2 degrees or less.

[0049] The optical film of the present invention exhibits excellent wavelength dispersion characteristics and viewing angle characteristics by laminating the films (A) and (B) in a state in which the angle between the fast axis of the film (A) and the fast axis of the film (B) is 90 degrees, that is, in a state in which the stretching directions of the films (A) and (B) are the same. Therefore, it is not necessary to cut two films in directions that form different angles and then bond them together, and a retardation film with high productivity can be obtained.

[0050] The film (A) and the film (B) may contain an antioxidant to improve the thermal stability. Examples of the antioxidant include hindered phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, lactone-based antioxidants, amine-based antioxidants, hydroxylamine-based antioxidants, vitamin E-based antioxidants, and other antioxidants. These antioxidants may be used alone or in combination of two or more. The films (A) and (B) may contain a hindered amine-based light stabilizer or an ultraviolet absorbing agent to improve weather resistance. Examples of the ultraviolet absorbing agent include benzotriazole, benzophenone, triazine, and benzoate.

[0051] Film (A) and film (B) may contain other polymers, surfactants, polymer electrolytes, conductive complexes, pigments, dyes, antistatic agents, antiblocking agents, lubricants, etc., within the scope of the invention.

[0052] The method for producing the films (A) and (B) of the present invention is not particularly limited, and they can be produced, for example, by forming a raw material resin into a long film by a method such as a solution casting method or a melt casting method, and stretching the film uniaxially or biaxially or more.

[0053] The method for producing the long film will be described below. Any method may be used as the method for producing the film, but it is preferable to produce it by a solution casting method. Here, the solution casting method is a method in which a resin solution (generally called a dope) is cast onto a support substrate, and then heated to evaporate the solvent to obtain a film. The coating method is not particularly limited, and a normal method can be adopted. For example, the T-die method, the doctor blade method, the bar coater method, the slot die method, the lip coater method, the reverse gravure coating method, the microgravure method, the spin coating method, the brush coating method, the roll coating method, the flexographic printing method, and the like can be mentioned. In addition, the support substrate to be used is not particularly limited, and examples thereof include polymer substrates made of polyester, polycarbonate, polystyrene, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride, triacetyl cellulose, polyvinyl alcohol, polyimide, polyarylate, polysulfone, polyethersulfone, epoxy resin, and the like, glass substrates such as glass plates and quartz substrates, metal substrates such as aluminum, stainless steel, and ferrotype, and inorganic substrates such as ceramic substrates, and the like can be mentioned. The substrate is preferably a polymer substrate or a metal substrate.

[0054] The solvent used in solution casting may be any solvent capable of dissolving resins, etc., but the boiling point of the solvent is preferably 200° C. or lower, more preferably 170° C. or lower, so that residual solvent is unlikely to remain during the film formation process.

[0055] Examples of the solvent include halogenated hydrocarbons such as chloroform, dichloromethane, carbon tetrachloride, dichloroethane, tetrachloroethane, trichloroethylene, tetrachloroethylene, chlorobenzene, and dichlorobenzene; phenols such as phenol and chlorophenol; aromatic hydrocarbons such as benzene, toluene, xylene, methoxybenzene, mesitylene, and dimethoxybenzene; acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, cyclopentanone, 2-pyrrolidone, N-methyl-2-pyrrolidone, and N-methyl-2-pyrrolidone. ketone-based solvents such as 2-pyrrolidone; ester-based solvents such as ethyl acetate and butyl acetate; alcohol-based solvents such as t-butyl alcohol, glycerin, ethylene glycol, triethylene glycol, ethylene glycol monomethyl ether, diethylene glycol dimethyl ether, propylene glycol, dipropylene glycol, and 2-methyl-2,4-pentanediol; amide-based solvents such as dimethylformamide and dimethylacetamide; nitrile-based solvents such as acetonitrile and butyronitrile; ether-based solvents such as diethyl ether, dibutyl ether, and tetrahydrofuran; and carbon disulfide, ethyl cellosolve, butyl cellosolve, etc., used alone or in mixture.

[0056] The viscosity of the resin solution when producing the film can be adjusted by the molecular weight and concentration of each component and the type of solvent. The viscosity of the resin solution is not particularly limited, but in order to facilitate film coating, it is preferably 100 to 30,000 cps, more preferably 300 to 20,000 cps, and particularly preferably 300 to 15,000 cps.

[0057] The drying method in the drying step of the coating solution is not particularly limited, and a common heating means can be used, such as a hot air blower, a heating roll, or a far infrared heater. In the film manufacturing method, the drying temperature may be in only one stage, or in order to maintain the appearance and shorten the drying time, multi-stage drying may be used in which the first stage is dried at a low temperature and the second and subsequent stages are dried at a high temperature.

[0058] In the present invention, the concentration of the raw resin in the dope is not particularly limited as long as dissolution and film formation are possible. The method of dissolving the resin composition may be carried out so that the concentration is a predetermined value at the dissolution stage, or it may be prepared as a low-concentration solution in advance and then adjusted to a predetermined high-concentration solution in a concentration process. Furthermore, it is also possible to prepare a high-concentration resin solution of the resin composition in advance, and then add various additives to prepare a low-concentration resin solution. The melt casting method is a molding method in which a resin is melted in an extruder, extruded into a film form from a slit in a T-die, and then taken up while being cooled by a roll or air.

[0059] The retardation is controlled by stretching the film uniaxially or biaxially, and the film can be made into the film (A) or film (B) constituting the laminated film of the present invention. Examples of the uniaxial stretching method include free width uniaxial stretching, stretching with a tenter, and stretching between rolls, while examples of the biaxial stretching method include stretching with a tenter and stretching by expanding into a tube shape. The stretching direction is preferably the film width direction or oblique direction.

[0060] The temperature during stretching is preferably 100° C. or higher and 300° C. or lower, particularly preferably 110° C. or higher and 250° C. or lower, since this results in a retardation film that is less prone to uneven thickness and has excellent mechanical and optical properties.

[0061] The stretching ratio of the film (hereinafter referred to as "stretching ratio") is preferably from 1.05 to 4.0, particularly preferably from 1.1 to 3.5, in order for the resulting film to exhibit good retardation properties. In this manner, by adjusting the stretching temperature and the stretching ratio, the in-plane retardation of the resulting stretched film can be controlled.

[0062] The transport speed of the resin film in the stretching step is preferably in the range of 0.5 m / min to 30 m / min in terms of machine precision, stability, etc., and more preferably in the range of 1 m / min to 20 m / min.

[0063] The manufacturing method of the present invention may include a shrinking step in which the film obtained by the stretching step is subjected to a shrinking treatment. Specifically, the stretched resin film is shrunk in the direction opposite to the stretching direction. This can relieve residual stress accumulated in the stretched resin film, and the obtained film exhibits high retardation even after a long period of time.

[0064] The thickness of the resin composition film to be subjected to the stretching step is preferably 5 to 200 μm, more preferably 5 to 150 μm, and particularly preferably 5 to 100 μm, from the viewpoints of ease of stretching treatment and suitability for thin optical members.

[0065] In order to prevent a decrease in the amount of light in the image display device, the film (A) and the film (B) preferably have a transmittance of 85% or more, more preferably 90% or more in the film form. The light transmittance here refers to the total light transmittance, and is a value measured at wavelengths of 380 nm to 780 nm using a device capable of measuring transmittance equipped with a white light source in accordance with JIS K 7361-1 (1997 edition). The total light transmittance here refers to a value measured when the composition contained in the optical film of the present invention is molded into a film having a thickness of 50 μm.

[0066] The haze of film (A) and film (B) is preferably 3.0% or less, more preferably 1.5% or less. By controlling the haze within the above range, a high-contrast image can be obtained when the film is incorporated into a display device as a retardation film. Here, the haze is a value measured at wavelengths of 380 nm to 780 nm using a general haze meter equipped with a white light source in accordance with JIS-K 7136 (2000 edition).

[0067] Film (A) and film (B) can be further laminated with a film containing other resins as required. Examples of other resins include polyethersulfone, polyarylate, polyethylene terephthalate, polynaphthalene terephthalate, polycarbonate, cyclic polyolefin, maleimide resin, fluorine resin, polyimide, etc. In addition, it is also possible to laminate a liquid crystal layer, a hard coat layer, a gas barrier layer, and a layer with a controlled refractive index (low reflection layer). The film (A) and the film (B) are preferably used in polarizing plates for use in liquid crystal displays, organic EL displays, etc. The polarizing plates are preferably used as image displays. EXAMPLES

[0068] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The physical properties shown in the examples were measured by the following methods.

[0069] <Polymer analysis> The polymer structure was analyzed using a nuclear magnetic resonance measuring device (manufactured by JEOL, product name: JNM-GX270) and proton nuclear magnetic resonance spectroscopy ( 1 H-NMR spectroscopy was used to determine the molecular weight. <Measurement of number average molecular weight> Gel permeation chromatography (GPC) equipment (Tosoh Corporation, product name: C0-8011 (column GMH HR The measurements were performed at 40°C using a 350-mm Filament Tube (equipped with a 350-mm Filament Tube) with tetrahydrofuran or dimethylformamide as a solvent, and the values ​​were calculated in terms of standard polystyrene.

[0070] <Measurement of phase difference characteristics> The retardation characteristics of the optical film were measured using a sample tilt type automatic birefringence meter (manufactured by Oji Scientific Instruments, product name: KOBRA-21ADH) with light having a wavelength of 589 nm. <Measurement of wavelength dispersion characteristics> The wavelength dispersion characteristics of the optical film were measured using a tilt-type automatic birefringence meter (manufactured by Oji Scientific Instruments, product name: KOBRA-21ADH, light source: halogen lamp (12V100W)) as the ratio of the phase difference Re(450) due to light with a wavelength of 450 nm to the phase difference Re(550) due to light with a wavelength of 550 nm.

[0071] Synthesis Example 1 In a 1-liter reactor equipped with a stirrer, a cooling tube, a nitrogen inlet tube, and a thermometer, 600 g of distilled water, 3.4 g of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., trade name Metolose 60SH-50) as a dispersant, 387.5 g of diisopropyl fumarate, 12.5 g of 3-ethyl-3-oxetanyl methyl acrylate (3.2 parts by weight per 100 parts by weight of diisopropyl fumarate), and 8.3 g of t-butyl peroxypivalate as an oil-soluble radical initiator were placed, and after nitrogen bubbling for 1 hour, radical suspension polymerization was carried out by maintaining the mixture at 50°C for 24 hours while stirring at 400 rpm. After the polymerization reaction was completed, the contents were recovered from the reactor, the polymerized product was filtered, washed twice with distilled water and twice with methanol, and then dried under reduced pressure at 80°C (yield: 73%). The number average molecular weight of the resulting fumaric acid ester polymer was 147,000. 1 H-NMR measurement confirmed that the polymer particles were diisopropyl fumarate-3-ethyl-3-oxetanylmethyl acrylate copolymers with a ratio of diisopropyl fumarate residue units to 3-ethyl-3-oxetanylmethyl acrylate residue units of 96.1 / 3.9 (mol %).

[0072] Synthesis Example 2 In a 1-liter reactor equipped with a stirrer, a cooling tube, a nitrogen inlet tube, and a thermometer, 600 g of distilled water, 3.4 g of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., trade name Metolose 60SH-50) as a dispersant, 400.0 g of diisopropyl fumarate, and 8.3 g of t-butyl peroxypivalate as an oil-soluble radical initiator were placed, and after nitrogen bubbling for 1 hour, radical suspension polymerization was carried out by holding at 50°C for 24 hours while stirring at 400 rpm. After the polymerization reaction was completed, the contents were recovered from the reactor, the polymerized product was filtered, washed twice with distilled water and twice with methanol, and then dried under reduced pressure at 80°C (yield: 77%). The number average molecular weight of the obtained diisopropyl fumarate polymer was 129,000.

[0073] Synthesis Example 3 In a 1-liter reactor equipped with a stirrer, a cooling tube, a nitrogen inlet tube, and a thermometer, 600 g of distilled water, 3.4 g of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., trade name Metolose 60SH-50) as a dispersant, 350.9 g of diisopropyl fumarate, 49.1 g of diethyl fumarate (14.0 parts by weight per 100 parts by weight of diisopropyl fumarate), and 8.3 g of t-butyl peroxypivalate as an oil-soluble radical initiator were placed, and after nitrogen bubbling for 1 hour, radical suspension polymerization was carried out by maintaining the mixture at 50°C for 28 hours while stirring at 400 rpm. After the polymerization reaction was completed, the contents were recovered from the reactor, the polymerized product was filtered, washed twice with distilled water and twice with methanol, and then dried under reduced pressure at 80°C (yield: 75%).

[0074] The number average molecular weight of the resulting fumaric acid ester polymer was 138,000. 1 H-NMR measurements confirmed that the polymer particles were copolymers of diisopropyl fumarate and diethyl fumarate with a molar ratio of diisopropyl fumarate / diethyl fumarate of 86.7 / 13.3.

[0075] Film Preparation Example 1 (Film (B) exhibiting positive birefringence) 20.0 g of polycarbonate resin (manufactured by Teijin) was dissolved in a methylene chloride solution to obtain a 20 wt% resin solution. The solution was cast onto a polyethylene terephthalate film using a coater, and dried in three stages at drying temperatures of 50°C, 80°C, and 155°C, and then peeled off from the polyethylene terephthalate film to obtain a film (resin composition) with a thickness of 8 μm. The obtained film was uniaxially stretched longitudinally at 144°C to 1.75 times the original thickness using a batch-type film biaxial stretching device. The obtained film had a thickness of 5 μm, an in-plane retardation Re=192 nm, an out-of-plane retardation Rth=101 nm, and R450 / R550=1.07.

[0076] Film Preparation Example 2 (Film (B) exhibiting positive birefringence) A film was produced in the same manner as in Film Production Example 1, except that the thickness of the raw film to be stretched (resin composition) was changed to 12 μm and the stretching method was changed to fixed width stretching. The film obtained had a thickness of 8 μm, an in-plane retardation Re of 198 nm, an out-of-plane retardation Rth of 190 nm, and R450 / R550 of 1.07.

[0077] Film Preparation Example 3 (Film (B) exhibiting positive birefringence) Except for changing the thickness of the raw film (resin composition) for stretching to 28 μm, a film was produced in the same manner as in Film Production Example 2. The obtained film had a thickness of 17 μm, an in-plane retardation Re of 339 nm, an out-of-plane retardation Rth of 300 nm, and R450 / R550 of 1.07.

[0078] Film Preparation Example 4 (Film (B) exhibiting positive birefringence) 15.0 g of polyarylate resin (manufactured by Unitika) was dissolved in a methylene chloride solution to obtain a 15 wt% resin solution. The solution was cast onto a polyethylene terephthalate film using a coater, and dried in three stages at drying temperatures of 50°C, 80°C, and 155°C. The film was then peeled off from the polyethylene terephthalate film to obtain a film (resin composition) with a thickness of 13 μm. The obtained film was uniaxially stretched longitudinally at 206°C to 1.75 times the original thickness using a batch-type film biaxial stretching device. The obtained film had a thickness of 10 μm, an in-plane retardation Re=170 nm, an out-of-plane retardation Rth=72 nm, and R450 / R550=1.10.

[0079] Film Preparation Example 5 (Film (B) exhibiting positive birefringence) A film was produced in the same manner as in Film Production Example 4, except that the thickness of the raw film to be stretched (resin composition) was changed to 25 μm and the stretching method was changed to fixed width stretching. The obtained film had a thickness of 15 μm, an in-plane retardation Re of 167 nm, an out-of-plane retardation Rth of 160 nm, and R450 / R550 of 1.10.

[0080] Film Preparation Example 6 (Film (B) exhibiting positive birefringence) Except for changing the thickness of the raw film (resin composition) to be stretched to 17 μm, a film was produced in the same manner as in Film Production Example 2. The film obtained had a thickness of 10 μm, an in-plane retardation Re of 228 nm, an out-of-plane retardation Rth of 201 nm, and R450 / R550 of 1.07.

[0081] Film Preparation Example 7 (Film (B) exhibiting positive birefringence) Except for changing the thickness of the raw film (resin composition) to be stretched to 10 μm, a film was produced in the same manner as in Film Production Example 1. The film obtained had a thickness of 7 μm, an in-plane retardation Re of 244 nm, an out-of-plane retardation Rth of 132 nm, and R450 / R550 of 1.07.

[0082] Example 1 19.4 g of the fumaric acid ester resin obtained in Synthesis Example 1 and 0.6 g of 2,6-diphenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine (molecular weight: 426) were dissolved in a toluene / methyl ethyl ketone = 9 / 1 (weight ratio) solution to obtain a 20 wt% resin solution. The solution was cast onto a polyethylene terephthalate film using a coater, and after two-stage drying at drying temperatures of 80 ° C. and 130 ° C., it was peeled off from the polyethylene terephthalate film to obtain a raw film (resin composition) for stretching with a thickness of 49 μm. The obtained film was uniaxially stretched longitudinally at 140 ° C. to 2.0 times the original thickness using a batch-type film biaxial stretching device. The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 1. The obtained film was excellent in viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0083] Example 2 A film was produced in the same manner as in Example 1, except that the thickness of the raw film to be stretched (resin composition) was changed to 91 μm and the stretching ratio was changed to 2.25 times. The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 1. The obtained film was excellent in viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0084] Example 3 A film was produced in the same manner as in Example 1, except that the thickness of the raw film to be stretched (resin composition) was changed to 45 μm. The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 1. The obtained film was excellent in viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0085] Example 4 19.2 g of the fumaric acid ester resin obtained in Synthesis Example 2 and 0.8 g of N,N'-diphenyl-N,N'-di(m-tolyl)benzidine (molecular weight: 517) were dissolved in a toluene / methyl ethyl ketone = 9 / 1 (weight ratio) solution to obtain a 20 wt% resin solution. The solution was cast onto a polyethylene terephthalate film using a coater, and after two-stage drying at drying temperatures of 80 ° C. and 130 ° C., it was peeled off from the polyethylene terephthalate film to obtain a raw film (resin composition) for stretching with a thickness of 51 μm. The obtained film was longitudinally uniaxially stretched at 140 ° C. to 2.25 times the original size using a batch-type film biaxial stretching device. The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 1. The obtained film was excellent in viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0086] Example 5 19.2 g of the fumaric acid ester resin obtained in Synthesis Example 3 and 0.8 g of 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine (molecular weight: 510) were dissolved in a toluene / methyl ethyl ketone=9 / 1 (weight ratio) solution to obtain a 20 wt% resin solution. The solution was cast onto a polyethylene terephthalate film using a coater, and the film was dried in two stages at drying temperatures of 80°C and 130°C, and then peeled off from the polyethylene terephthalate film to obtain a raw film (resin composition) for stretching having a thickness of 54 μm. The obtained film was uniaxially stretched longitudinally at 140°C to 1.4 times the original thickness using a batch-type film biaxial stretching device. The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 1. The obtained film was excellent in viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0087] Example 6 A film was produced in the same manner as in Example 1, except that the thickness of the raw film to be stretched (resin composition) was changed to 21 μm and the stretching ratio was changed to 1.4 times. The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 1. The obtained film was excellent in viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0088] Example 7 A film was produced in the same manner as in Example 4, except that the thickness of the raw film to be stretched (resin composition) was changed to 22 μm and the stretching ratio was changed to 1.4 times. The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 1. The obtained film was excellent in viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0089] Example 8 The two films of Example 1 and Film Preparation Example 1 were stretched in such a manner that the stretching axes were aligned (the progress of the two films The films were laminated together so that their phase axes were perpendicular (90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are shown in Table 2. The obtained film had excellent viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0090] Example 9 The two films of Example 1 and Film Preparation Example 2 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are shown in Table 2. The obtained film had excellent viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0091] Example 10 The two films of Example 2 and Film Preparation Example 3 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are shown in Table 2. The obtained film had excellent viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0092] Example 11 The two films of Example 3 and Film Preparation Example 4 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are shown in Table 2. The obtained film had excellent viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0093] Example 12 The two films of Example 3 and Film Preparation Example 5 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are shown in Table 2. The obtained film had excellent viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0094] Example 13 The two films of Example 4 and Film Preparation Example 6 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are shown in Table 2. The obtained film had excellent viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0095] Example 14 The two films of Example 5 and Film Preparation Example 7 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are shown in Table 2. The obtained film had excellent viewing angle characteristics and reverse wavelength dispersion characteristics, and was suitable as an optical film.

[0096] Comparative Example 1 19.6 g of the fumaric acid ester resin obtained in Synthesis Example 1 was dissolved in a toluene / methyl ethyl ketone=9 / 1 (weight ratio) solution without adding a wavelength dispersion regulator to obtain a 20 wt% resin solution. The solution was cast onto a polyethylene terephthalate film using a coater, and dried in two stages at drying temperatures of 80°C and 130°C, and then peeled off from the polyethylene terephthalate film to obtain a raw film (resin composition) for stretching with a thickness of 84 μm. The obtained film was uniaxially stretched longitudinally at 140°C to 1.2 times the original thickness using a batch-type film biaxial stretching device. The film thickness, retardation property, and wavelength dispersion property of the obtained optical film were measured. The results are shown in Table 1. The obtained film did not exhibit reverse wavelength dispersion properties and was unsuitable as an optical film.

[0097] Comparative Example 2 A film was produced in the same manner as in Comparative Example 1, except that 19.6 g of the fumaric acid ester resin obtained in Synthesis Example 1 and 0.4 g of the plasticizer diisodecyl adipate (molecular weight: 427) were dissolved in a toluene / methyl ethyl ketone = 9 / 1 (weight ratio) solution to prepare a 20 wt% resin solution, and the thickness of the raw film for stretching (resin composition) was changed to 82 μm. The film thickness, retardation property, and wavelength dispersion property of the obtained optical film were measured. The results are also shown in Table 1. The obtained film did not exhibit reverse wavelength dispersion properties and was unsuitable as an optical film.

[0098] Comparative Example 3 The two films of Comparative Example 1 and Film Preparation Example 1 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 2. The obtained film was thick and had insufficient reverse wavelength dispersion characteristics, and was therefore unsuitable as an optical film.

[0099] Comparative Example 4 The two films of Comparative Example 2 and Film Preparation Example 4 were laminated together so that their stretching axes coincided (the fast axes of the two films were perpendicular to each other by 90 degrees). The film thickness, retardation characteristics, and wavelength dispersion characteristics of the obtained optical film were measured. The results are also shown in Table 2. The obtained film was thick and had insufficient reverse wavelength dispersion characteristics, and was therefore unsuitable as an optical film.

[0100] [Table 1]

[0101] [Table 2]

Claims

1. An optical film comprising an ester resin exhibiting negative birefringence and a wavelength dispersion regulator having a molecular weight of 300 to 1,000 and exhibiting positive birefringence, wherein the relationship between the refractive index in the fast axis direction in the film plane, the refractive index in the film plane direction perpendicular thereto, and the refractive index in the vertical direction outside the film plane, nx, ny, and nz, respectively, is nx<ny≦nz, and the ratio (R450 / R550) of the in-plane retardation (R450) measured at a wavelength of 450 nm and the in-plane retardation (R550) measured at a wavelength of 550 nm, as shown in formula (a), is 1.00 or less. Re=(ny-nx)×d (a) (In the formula, nx represents the refractive index in the fast axis direction in the film plane, ny represents the refractive index in the slow axis direction in the film plane, nz represents the refractive index in the vertical direction outside the film plane, and d represents the thickness of the film.)

2. 2. The optical film according to claim 1, wherein the wavelength dispersion regulator exhibiting positive birefringence is an aromatic compound.

3. 3. The optical film according to claim 1, wherein the wavelength dispersion adjuster exhibiting positive birefringence is at least one member selected from the group consisting of benzotriazole-based compounds, benzophenone-based compounds, triazine-based compounds, benzoate-based compounds, and polyphenyl-based compounds.

4. 4. The optical film according to claim 1, wherein the content of the wavelength dispersion regulator in the composition contained in the film is from 0.01% by weight to 30% by weight.

5. 5. The optical film according to claim 1, wherein the ester resin exhibiting negative birefringence contains 50 mol % or more of a fumaric acid ester residue unit represented by the following formula (1): [Formula 1] (In the formula, R 1 and R 2 each independently represents one of the group consisting of a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, or a cyclic alkyl group having 3 to 6 carbon atoms.

6. The optical film according to any one of claims 1 to 5, characterized in that the film has a thickness of 80 μm or less, an Re measured at a wavelength of 589 nm of 120 nm to 700 nm, and an out-of-plane retardation (Rth) measured at a wavelength of 589 nm and represented by formula (b) is -700 nm to -60 nm. Rth=[(nx+ny) / 2-nz]×d (b)

Citation Information

Patent Citations

  • Manufacturing method of birefringent film, retardation plate and liquid crystal display device using the same

    JP1993297223A

  • Production of double refraction film, phase shifter and liquid crystal display device

    JP1993323120A

  • Production of double refraction film and liquid crystal display device using the double refraction film

    JP1994088909A

  • Retardation film

    JP2005156862A

  • Retardation film

    JP2008129465A